Prohibition's Greatest Myths : The Distilled Truth about America's Anti-Alcohol Crusade - Hamm, Richard F.; Lewis, Michael, 1965- (Book collections on Project MUSE., 2020)
"As a prominent historian recently noted in the Washington Post, 'The common understanding of the Prohibition Era is based more on folklore than fact.' This volume aims to correct common misconceptions about American prohibition in ten essays from scholars who have spent their careers studying different aspects of the era. Each contributor unravels one myth and reveals the historical evidence that supports, refutes, or complicates a deeply embedded misunderstanding. Paul Thompson takes on the myth that temperance and prohibition were the same and that the movements shared the same goals and tactics. Joe Coker shows that it was religious liberals, not conservatives, who spearheaded the prohibition movement. Lisa Andersen slays the persistent idea that prohibitionists were trying to legislate individual behavior, and Ann-Marie Szymanski shows that World War I was the primary cause for the enactment of national prohibition. Michael Lewis debunks the idea that alcohol consumption increased during the era. Richard Hamm shows that prohibition did not start organized crime. Thomas Pegram shows that the failure of prohibition alone did not lead to its repeal, while Mark Schrad shows that prohibition was not uniquely American but a worldwide phenomenon. Garret Peck reveals that prohibition had a long-term effect on American drinking habits, and Robert Beach discredits the idea that the current debates over marijuana legalization are the same as those Americans had during the 1930s that ended prohibition. Together the essays unravel embedded myths and provide a much more nuanced understanding of the prohibition era. Such an understanding will allow readers to engage more meaningfully in contemporary alcohol and drug policy debates"--